Crangonyx islandicus sp. nov., a subterranean freshwater amphipod (Crustacea, Amphipoda, Crangonyctidae) from springs in lava fields in Iceland - Svavarsson, J.; Kristjánsson, B. K. (Zootaxa, 2006)
Crangonyx islandicus sp. nov. (Crustacea, Amphipoda, Crangonyctidae) is described from Iceland. This is the second species of freshwater, subterranean, gammaridean amphipods found in Iceland and the first species of the family Crangonyctidae. Crangonyx islandicus sp. nov. can be distinguished from other species of the genus Crangonyx by combination of the following characters: the number of spines on the outer and inner lobes of the maxillipedal palp, the presence of a spine at the base of the unguis of the dactylus of gnathopods 1 and 2, stout and short uropod 3, and by a short and wide telson. The species was recorded in South, Southwest, West and Northeast Iceland from numerous springs emerging from relatively young (